Viscous Ricci Dark Energy Cosmological Models In Brans-Dicke Theory - Vijaya Santhi, M.; Chinnappalanaidu, T.; Srivani Madhu, S. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
The whole article deals with the analysis of the cosmic model of Ruban's space-time in the context of a bulk viscosity impact in the form of Ricci dark energy within the framework Brans- Dicke theory. We believe that outer space is filled with dark matter and viscous Ricci dark energy (VRDE) under the pressureless situation. Статья посвящена анализу космической модели пространства времени Рубана в контексте воздействия объемной вязкости в форме темной энергии Риччи в рамках теории Бранса-Дикке. Мы считаем, что внешний космос заполнен темной материей и вязкой темной энергией Риччи (VRDE) в условиях отсутствия давления.
Keywords: Astrophysics